Administration of Adenosine Triphosphate Provides Additional Value Over Programmed Electrophysiologic Study in Confirmation of Successful Ablation of Atrioventricular Accessory Pathways - Wei, Wei; Fang, Xianhong; Shehata, Michael; Wang, Xunzhang; Zhan, Xianzhang; Deng, Hai; Liao, Hongtao; Liao, Zili; Liu, Yang; Xue, Yumei; Wu, Shulin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To study the benefit of adenosine triphosphate (ATP) in evaluating ablation endpoints of accessory pathways (AP) and subsequent long-term prognosis. Methods: We reviewed consecutive patients with supraventricular tachycardias due to APs that underwent radiofrequency catheter ablation (RFCA) from January 2016 to September 2018 in our center. The patients were divided into two groups: the ATP group (who had passed both the ATP test and PES after ablation as the endpoint) and the non-ATP group (who had passed PES only after ablation as the endpoint). We reviewed the patients' intra-cardiac electrograms and analyzed their long-term outcomes. Results: In total, 1,343 patients underwent successful RFCA. There were 215 patients in the ATP group with one lost to follow-up. There were 1,128 patients in the non-ATP group with 39 lost to follow-up. Twenty-three patients in the ATP group demonstrated additional electrophysiological entities due to ATP administration, including reappearance of the ablated APs in 16 patients, discovery of PES-undetected APs in 5, induction of atrial fibrillation in 5, premature atrial contractions in 1, and premature ventricular contractions in another. During the 7 to 39 months (average 24.4 ± 9.5 months) follow-up, the recurrence rate was 8.41% (18/214) in the ATP group and 6.80% (74/1,084) in the non-ATP group. In subjects with recurrence, 14 patients (14/18 = 77.8%) in the ATP group and 50 patients (50/74 = 67.6%) in the non-ATP group accepted redo ablations. Among the ATP-group, all the 14 redo APs were the old ones as before. Among the non-ATP-group, redo ablations confirmed that 39 APs were the old ones, while 20 APs were newly detected ones which had been missed previously. The difference in recurrent AP locations confirmed by redo procedures between the two groups was significant (p = 0.008). In the non-ATP group, 20 (40%) of redo cases were proven to have multiple APs, while 33 (3.3%) cases who did not suffer from recurrence had multiple APs. Existences of multiple APs in recurred cases were significantly higher than that in non-recurred ones in the non-ATP group (p < 0.001), while there was no such difference in the ATP group (p = 0.114). Conclusions: The existence of multiple APs was more common in recurrent cases if ATP was not used for confirmation of ablation endpoints. ATP probably has additional value over PES alone by detecting weak AP conductions. ATP can evoke atrial and ventricular arrhythmias.